PENGARUH PENJUALAN KONVENSIONAL DAN PENJUALAN E-COMMERCE TERHADAP KEPUTUSAN PEMBELIAN MENGGUNAKAN METODE REGRESI (Jurnal Pariwisata Bisnis Digital dan Manajemen, 2024)
The widespread use of e-commerce in the digital era has increased information disclosure while changing the way consumers make purchases. Consumer decisions are influenced by several factors, including the influence of technology, price and product comparison, information disclosure, and ease of access. The purpose of this study is to use regression analysis to examine the impact of traditional and online sales on PT Airlangga Jaya Mandiri. This study also looks at additional factors that can influence consumer purchasing decisions and determine the relationship between the variables studied. The regression analysis of PT Airlangga Jaya Mandiri, however, shows that neither traditional sales nor online sales significantly affect the dependent variable in this study. The resulting constant value is 1.740, and has a coefficient for conventional sales of 0.057 and a coefficient for E-commerce sales of -0.020. Although the p value is greater than 0.05, indicating statistical insignificance, further research and data collection is needed to confirm the relationship between these variables and consider other factors that may affect the dependent variable. The results of this study provide insights for businesses in developing more effective marketing strategies and improving customer service, with the understanding that the factors that consequence purchase decisions may be more complex than revealed in this regression model
Keywords: conventional; e-commerce; linear_regression_analysis; purchase decisions; sales